T2 Magnetic Resonance to Monitor Hemostasis - Cuker, Adam; Marturano, Joseph E.; Carinato, Maria E.; Lowery, Thomas J.; Cines, Douglas B. (Seminars in Thrombosis and Hemostasis, 2019)
There is a clinical need for pragmatic approaches to measure integrated hemostatic reactions in whole blood rapidly, using small volumes of blood. The authors have applied T2 magnetic resonance (T2MR) to assess coagulation reactions based on partitioning of red blood cells and proteins that occurs during fibrin formation and platelet-mediated clot contraction. T2MR is amenable to measuring clotting times, individual coagulation factors, and platelet function. T2MR also revealed a novel “hypercoagulable” signature characterized by fibrin clots almost insusceptible to fibrinolysis that surround tessellated arrays of polyhedral erythrocytes (“third peak”). This signature, which develops under conditions associated with intense clot formation in vitro, may help identify patients at risk of developing thrombosis and for monitoring antithrombotic therapies in the future.
Keywords: hemostasis; fibrin; T2 magnetic resonance; platelet function